Pengaruh Daya Tarik Wisata dan Citra Destinasi Terhadap Niat Berkunjung Kembali yang Dimediasi oleh Memorable Tourism Experience - Anggraeni, Putu Winda Putri; Antara, Made; Ratna Sari, Ni Putu (JURNAL MASTER PARIWISATA; Volume 09, Nomor 01, Juli 2022DO - 10.24843/JUMPA.2022.v09.i01.p08, 2022)
This research was designed to investigate the effect of tourist attraction and destination image on revisit intentions mediated by the memorable tourism experience at Jatiluwih Tourist Attraction. This research uses a quantitative method. Questionnaires were distributed to 145 domestic tourists who had visited the Jatiluwih Tourist Attraction during the new normal era. Afterward, the analysis of Structural Equation Model (SEM) was conducted by using Smart-PLS 3.3. The result of this research indicates that: 1) Tourist attraction has significant effect on revisit intention. 2) Destination image has significant effect on revisit intention. 3) Tourist attraction has significant effect on memorable tourism experience. 4) Destination image has no significant effect on memorable tourism experience. 5) Memorable tourism experience has significant effect on revisit intention. 6) Tourist attraction has significant effect on revisit intention through memorable tourism experiences as a mediating variable. 7) Destination image has no significant effect on revisit intention through memorable tourism experiences as a mediating variable. Keywords: tourist attraction, destination image, memorable tourism experiences, revisit intention.